(untitled) (Research, Society and Development, 2023)
Brazilian road infrastructure plays a prominent role in the country’s socioeconomic development, both at a regional and national level. However, the road sector faces difficulties related to the lack of investment to expand the road network or preventive and corrective maintenance of highways in operation. The present research work aimed to evaluate the performance parameters of a highway pavement. For this purpose, the 2006 National Department of Transport Infrastructure (DNIT) Paving Manual and the procedures adopted by DNIT standard 008/2003 were the guiding parameters for the development of the study. The highway studied, named Avenida Jatobá, is located in the Cohab II neighborhood, in the city of Sobral, Ceará, Brazil. Based on data collection and on-site studies, an analysis of the pavement’s performance was carried out, considering several factors such as safety, comfort and economy. Furthermore, it was possible to evaluate the state of conservation of the pavement, as well as identify the main agents that cause pathologies on the highway, and thus propose solutions to solve detected problems. The study showed that the pathologies found on the pavement could come from several factors such as: inadequate execution of the work, lack of preventive maintenance, inefficient projects, among others. The results of the degree of aggressiveness of the highway show signs that the defects have reached the structural layers of the pavement, making it extremely important to carry out a more in-depth survey test to identify a safer and more appropriate measure. In turn, it would be necessary to carry out structural recovery of the entire section.